1991
DOI: 10.3382/ps.0700923
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diet and Population Density on Male Turkeys Under Various Environmental Conditions.

Abstract: The performance of 1,312 male market turkeys (Large White, Nicholas strain) from 0 to 20 wk of age fed diets varying in feed form and energy level was measured under two stocking densities (.21 or .46 m2 per bird) and four lighting and temperature programs. The four diets were 1) corn and soybean meal with 1% supplemental fat, mash (CSM); 2) as 1, pelleted (CSP); 3) as Diet 1 but with 1, 2, 4, 6, and 8% supplemental fat during 0 to 4, 4 to 8, 8 to 12, 12 to 16, and 16 to 20 wk of age, respectively (CSF); and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 18 publications
2
23
2
Order By: Relevance
“…While feed conversions were better (P < 0.001) for the birds given the pelleted feeds (FMP or CMP, Table 4), lower feed intakes (P < 0.001) and 84-d body weights (P < 0.05) occurred for these birds than those fed the mash feeds (FM or CM). These results do not agree with those of Pepper et al (1962), Revington and Moran (1990) or Noll et al (1991) who reported higher body weights and improved feed conversion values for turkeys fed pelleted than those given mash feeds. Also, Proudfoot and Hulan (1982) reported that as the level of "fines" increased in pelleted grower and finisher feeds, feed conversion values were not as efficient and body weights decreased (P > 0.05).…”
Section: Resultscontrasting
confidence: 93%
See 1 more Smart Citation
“…While feed conversions were better (P < 0.001) for the birds given the pelleted feeds (FMP or CMP, Table 4), lower feed intakes (P < 0.001) and 84-d body weights (P < 0.05) occurred for these birds than those fed the mash feeds (FM or CM). These results do not agree with those of Pepper et al (1962), Revington and Moran (1990) or Noll et al (1991) who reported higher body weights and improved feed conversion values for turkeys fed pelleted than those given mash feeds. Also, Proudfoot and Hulan (1982) reported that as the level of "fines" increased in pelleted grower and finisher feeds, feed conversion values were not as efficient and body weights decreased (P > 0.05).…”
Section: Resultscontrasting
confidence: 93%
“…While light intensity and length of photoperiod have significant effects on the performance, health and behaviour of turkeys (Cunningham 1993), few results have been published concerning these factors (Buckland 1975;Cunningham 1993). When compared with continuous lighting schedules, the body weights of turkeys grown with a intermittent lighting schedule were higher even though they consumed less feed (Buckland 1975;Hulan et al 1980;Siopes et al 1986;Noll et al 1991). Mortality also has been found to be lower when turkeys were subjected to an increasing photoperiod schedule compared to those receiving continuous light (Newberry 1992;Classen et al 1994); however, the effect of increasing lighting on the performance of the birds reported by Newberry (1992) was inconclusive.…”
mentioning
confidence: 99%
“…It is important to note that the highest weight gain occurred in the 18L:6D group, whereas the lowest weight gain was observed in the 12L:12D group in both the first 10 and the last 6 weeks of the study. The results of the feed intake of turkeys are similar to those of other studies in the literature (HALVORSOR et al, 1991;NOLL et al, 1991;CLARKE et al, 1993;SENGUL et al, 2000). On the other hand, maximum live weight difference among three lighting programs throughout first 10 weeks (3473.5 g) was notably higher than the weight gain (2208 g) observed throughout last 6 weeks.…”
Section: Methodssupporting
confidence: 81%
“…Though feeder space per bird was the same in each treatment, this growth depression may have been the consequence, at least partly, of more disturbance or competition during the feeding activity. The results of T2 demonstrated that the relationship might be inconsistent and not linear, as found in previous studies (Coleman and Leighton, 1969;Proudfoot et al, 1979;Denbow et al, 1984;Moran, 1985;Noll et al, 1991).…”
Section: Discussionmentioning
confidence: 49%
“…It is well documented that the final weight of turkey broilers decreases when stocking density increases (Coleman and Leighton, 1969;Proudfoot et al, 1979;Denbow et al, 1984;Moran, 1985;Noll et al, 1991). On the other hand, although many authors have considered the effect of density on behavioural and health traits of chicken broilers (Ekstrand, 1993), few studies have concerned turkey broilers (Denbow et al, 1984;Leighton et al, 1985;Moran, 1985;Ekstrand and Algers, 1997).…”
Section: Introductionmentioning
confidence: 98%